Genealogía de doña Francisca de Guzmán, Xochimilco, 1610 - Reyes García, Luis (Tlalocan, 2013)
he anthropologist Luis Reyes publishes here an early Seventeenth Century document dealing with the genealogy of a native noblewoman of Xochimilco. Her ancestors, members of the reigning family in Tenochtitlan, are traced back to the Fourteenth Century.